DIFFICULTIES IN TEACHING FOREIGN LANGUAGES TO YOUNG LEARNERS. - Alijonova Gulhayo,; Jalolova M, (TADQIQOTLAR, 2025)
In recent decades, early foreign language education has gained increasing global attention.  Many  educators  and  policymakers  advocate  for  introducing  foreign languages at the primary school level, arguing that younger learners have a natural ability  to  acquire  new  languages  more  effectively  than  adolescents  or  adults (Lightbown  &  Spada,  2013).  Indeed,  children  possess  greater  neural  plasticity  and imitate sounds more accurately, which makes them ideal candidates for early language instruction (Lenneberg, 1967). However, despite these advantages, teaching foreign languages to young learners presents a number of complex challenges that are often overlooked.